Integrasi Budaya Islam Indonesia dalam Pengembangan Soal HOTS untuk Mengoptimalkan Kemampuan Berpikir Kritis Siswa - Oktiningrum, Wuli; Wardhani, Dyah Ayu Pramoda; Muslihasari, Adzimatnur; Wibowo, Andi (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2025)
Critical thinking skills are very important. However, many students in Indonesia have low critical thinking skills. This study developed HOTS questions with the context of Indonesian Islamic culture to improve the critical thinking skills of elementary school students. The method used is the development research method, which consists of analysis, design, evaluation, and revision. The stages of developing these questions go through preliminary and prototyping stages with a formative evaluation flow. A total of 50 6th-grade students from SD Negeri 1 Dilem and SD Negeri 1 Mangunrejo Malang Regency became the subjects of this study, as well as three experts involved in the prototyping stage. Data were collected using walk-through, documentation, questionnaires, tests, and interviews. This study produced 5 HOTS questions in the context of Indonesian Islamic culture, with valid, practical, and potential effect categories. Based on the results of the analysis, prototype 3 has the potential to measure the critical thinking skills of elementary school students, as shown through student answers. Students' critical thinking skills are assessed based on four indicators: 1) interpretation, namely 90% of students show understanding by identifying the information given and requested accurately; 2) analysis, with 70% of students successfully establishing relationships between statements, questions, and concepts through mathematical modeling and appropriate explanations; 3) evaluation, where 50% of students applied proper procedures to solve and calculate problems correctly; and 4) conclusion, where 45% of students were able to formulate conclusions correctly based on their solution steps. Another indication of effectiveness is also seen in the seriousness and interest of students when solving problems. Recommendations for further research include developing problems in more diverse contexts, with the context of Indonesian culture.